Prosthetic robotic arm with patient monitoring system for children - Abdul Nasir, Abd Ghafar; Nadarajah, Devin Babu; Muhammad Hafizuddin, Abd Latiff; Muhammad Lutfir Rahman, Ahmad Safuan (2021)
Prosthetic robotic arm are becoming crucial needs for children with forearm amputation or disabilities but the cost are expensive. Children with forearm amputation face various obstacles related to regular activities such as holding and grasping the objects or tools. Monitoring system especially for disabled people has been an essential features in order to improve Quality of Life (QOL).